TindakTutur Direktif dalam Novel Cinta Suci Zahrana Karya Habiburrahman El Shirazy - Putri Bungsu; Saifuddin Mahmud; Armia Armia (JIM Pendididikan Bahasa dan Sastra Indonesia, 2020)
This study is entitled "Directives' Speech Acts in the novel Cinta Suci Zahrana by Habiburrahman El Shirazy". The formulation of the problem is how the directive speech acts ask, ask, order, forbid, permit, and advise in the novel Cinta Suci Zahrana by Habiburrahman El Shirazy. The purpose of this study is to explain the directive speech acts of asking, asking, ordering, banning, permitting, and advising in the novel Cinta Suci Zahrana by Habiburrahman El Shirazy. The research benefit is that theoretically this study can broaden the horizon regarding speech act so that it is useful for other researchers and practically this research is useful to better understand directive speech act theory especially novels and can be used by teachers in teaching material. The approach method used in this research is a qualitative approach in a descriptive-qualitative system. The data of this study came from speech contained in interpersonal dialogue, while the source of the data was the novel Cinta Suci Zahrana by Habiburrahman El Shirazy. Data collection is done by document review techniques, observation techniques, and recording techniques. The results prove that there are six directive speech acts described in Habiburrahman El Shirazy's novel Cinta Suci Zahrana consisting of directive speech acts asking, directive speech acts asking, directive speech acts commanding, directive speech acts prohibiting, directive speech acts allow, and directive speech acts. directive advising. Of the six directive speech acts, 268 data consisted of 82 directive speech acts asking, 121 directive speech acts asking, 18 directive speech acts, 30 directive speech acts, forbid, 8 directive speech acts allow, and 9 directive speech acts. the directive said advising. Of the 268 data that have been analyzed, the directive speech act of asking is the directive speech act most commonly found in the dialogue dialogue of the novel Cinta Suci Zahrana by Habiburrahman El Shirazy